(untitled) (ModaPalavra e-periódico, 2014)
The fashion drawing is a valuable tool for communicating ideas and concepts related to the development of apparel. In its process is necessary to consider that each fabric has its own properties and its interaction with the human body generates several effects that need to be represented precisely in order to achieve a result that is coherent with the reality. The study of fabric behavior is called draping and this current paper examines how it is expressed in fine arts and fashion drawing, aiming to incorporate this concept to a teaching practice based on the construction of knowledge and therefore aligned to the capacity of a creative professional who is able to propose innovative solutions.